Anakku, ayah & bunda sayang kamu ! / Abdullah Muhammad Abdul Muthi; penerjemah, H. Wafi Marzuki Ammar; editor, Ainul Haris Umar Thoyyib, Waznin Mahfuzh, J. Hariyadi - ABDULLAH MUHAMMAD ABDUL MU'THI; Wafi Marzuki Ammar , H.; Ainul Haris Umar Thoyyib; Waznin Mahfuzh; Hariyadi, J. (Pustaka Yassir, 2015)
573 hlm. : ilus. ; 24 cm.